STUDY REGARDING THE ROLE OF THE SIMULATOR AND MODERN TECHNIQUES ON ERROR SCREENING AND CORRECTION OF SOME SPECIFIC MOVES ON PERFORMANCE SWIMMERS - Silviu ȘALGĂU (Editura Universitatii Transilvania din Brasov, 2018)
Swimming is one of the performance sports with a high effort demand for the youth. To get superior performances, the swimmer or the sportsman, in general, needs to act in favor of development of all motion‐related qualities involved into the aquisition of that said performance. The studies and researches confirmed that there is no motion without a force, and an improper education of this attribute makes even impossible the formation and consolidation of the motrical behaviours. The computer‐aided simulator grants the possibility to highlight and measure the neuromuscular processes, giving access to an objective, instant information. This kind of information permits corrections of the technique in real time, during the motion, and corrections for the motion parameters during the motric act or when transitioning from one kind of motion to another (in the case of cyclic sports). The use of the simulator is augmented by other modern techniques (video in‐water recordings, both front and profile, and software programs, namely MaxTRAQ).The study is focused largely on the analysis of training the performance swimmers, having a dominant attraction to the crawl swimming procedure.